ENHANCING STUDENT ENGAGEMENT THROUGH THE THINK-PAIR-SHARE (TPS) MODEL: CAN THE TEACHING OF AQIDAH AND AKHLAK BE MORE EFFECTIVE? - Disti Nupita Sari; Farida Farida; Agus Susanti (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
The learning of Aqidah Akhlak at MTs Negeri 03 Muara Enim faces challenges in the form of low participation, lack of courage for students to ask questions, and the dominance of lecture methods that trigger passivity. The main problem of this research is to test the effectiveness of the Think Pair Share model in transforming student learning activity. The research steps used a quasi-experimental quantitative approach involving 25 students from the experimental class and 27 students from the control class in the odd semester of 2025/2026. Crucial stages include the distribution of an activity questionnaire that measures physical, mental, and emotional dimensions, followed by statistical analysis of the t-test. The quantitative research findings through the Independent Sample T-Test showed a significance value of 0.022, which is far below the threshold of 0.05. The data confirms the existence of a very real difference in activity between the two groups, proving that systematic interaction in the thinking, pairing, and sharing stages is able to trigger active student involvement significantly. The main conclusion confirms that this model has great potential to improve the instructional quality of Islamic education, although its success is still influenced by individual self-confidence and conducive classroom dynamics. Adapting strategies to heterogeneous groups is highly recommended to optimize learning outcomes sustainably and achieve a deep moral understanding for all students in the madrasah environment through active, meaningful and targeted collaboration in shaping the noble character of Indonesia's young generation.